Educational Crisis and Scientific Design in Education - Massimo Baldacci (Pensa MultiMedia, 2022)
The paper examines two types of educational crisis. The first type crisis as a transition in the ethicality of a social community. And the crisis of the second type as a fading of ethicality. Pedagogical responses to these types of crises are also examined.